Confinement and semi confinement of lambs in an integrated production system: impacts on production performance, infection by gastrointestinal nematodes, and selected blood analytes - dos Santos Schmidt, Elizabeth Moreira [UNESP]; Fachiolli, Daniele Floriano [UNESP]; de Lima Meirelles, Paulo Roberto [UNESP]; de Soutello, Ricardo Velludo Gomes [UNESP]; Pariz, Cristiano Magalhães [UNESP]; de Castilhos, André Michel [UNESP]; do Amarante, Alessandro Francisco Talamini [UNESP]; de Almeida, Fabiana Alves [UNESP]; de Souza, Daniel Martins [UNESP]; da Silva Barros, Juliana [UNESP]; Costa, Ciniro [UNESP] (FapUNIFESP (SciELO), 2024)
ABSTRACT: This trial evaluated the production performance, gastrointestinal nematode infection (GIN), and selected blood analytes, in Corriedale lambs during the finishing phase in an integrated crop-livestock system (ICLS) with 2 stocking rates. Fifty-two Corriedale lambs were divided into 4 groups: a semi confinement system with a low stocking rate (T1) for 70 days; a semi confinement system with a high stocking rate (T2) for 70 days; confinement for 28 days, followed by semi confinement with a low stocking rate (T3) for 42 days; and confinement for 28 days, followed by semi confinement with a high stocking rate (T4) for 42 days. Body weight, dry matter intake, blood collection, and faecal analysis of nematode eggs were performed for each animal. The stocking rates did not influence body weight gain for the semiconfined lambs (T1 and T2) or for the confined/semiconfined lambs (T3 and T4). All treatments had lower EPG counts at the end of the experimental period. The nematode genera identified during the experiment trial were Haemonchus and Trichostrongylus. There were no significant differences (P > 0.05) for packed cell volume, total plasma protein, and eosinophil means between treatments. These results suggested that the confinement followed by semi confinement in an ICLS, was an option for lamb production during the finishing phase which could be useful in reducing GIN without affecting the production performance. RESUMO: O objetivo deste experimento foi avaliar o desempenho produtivo, infecção por nematódeos gastrointestinais (GIN) e variáveis sanguíneas selecionadas, em cordeiras Corriedale durante a fase de terminação em sistema integrado lavoura-pecuária (ICLS) com duas taxas de lotação. O experimento utilizou 52 cordeiras Corriedale divididas em quatro grupos: sistema de semiconfinamento com baixa taxa de lotação por área (T1) por 70 dias; sistema de semiconfinamento com alta lotação por área (T2) por 70 dias; confinamento por 28 dias, seguido de semiconfinamento com baixa lotação por área (T3) por 42 dias; e confinamento por 28 dias, seguido de semiconfinamento com alta lotação por área (T4) por 42 dias. Peso corporal, ingestão de matéria seca, coleta de sangue e análise fecal para ovos de nematódeos foram avaliados para cada animal. As taxas de lotação não influenciaram no ganho de peso dos cordeiros semiconfinados (T1 e T2) ou nos confinados/semiconfinados (T3 e T4). Todos os tratamentos apresentaram contagens menores de EPG no final do período experimental. Os gêneros de nematódeos identificados durante o experimento foram Haemonchus e Trichostrongylus. Não houve diferença significativa (P > 0.05) para hematócrito, proteína plasmática total e média de eosinófilos entre os tratamentos. Esses resultados sugerem que o confinamento seguido de semiconfinamento em ICLS pode ser uma opção para a produção de cordeiras na fase de terminação e pode ser útil para a redução da GIN sem afetar o desempenho da produção.